Analisis Dampak Kurs Mata Uang Inflasi dan Pertumbuhan Ekonomi terhadap Return Saham: Studi pada Ferusahaan Multinasional di Bursa Efek Jakarta - Chalasina Violend Tiven; Elok Pakaryaningsih (Jurnal Riset Manajemen dan Bisnis, 2006)
The main objective of this study is to provide empirical evidence of the effect of macro economic factors on stock return. Moreover, this study is focused on multinational corporations due to their specific characteristics which are constantly reluctant to macro economic fuctors, especially foreign currency changes. This reluctantly, therefore triggered stock price changes.The sample is taken using non-probability random sampling in year 2000-2044 and resulted on 3 5 companies which are consistent with sample criteria. Subsequently, the data were analyzed using pooled least squares regression.The independent variables for the model are inflation, gross domestic product and currency exchange rates, whilst the dependent variqble for the model is daily abnormal returns which ore occumulated during a year (CAR). The resultof this study shows positive ffict of inflation on stock returns and negative effect of domestic product on stock returns. On the contrary, exchange rates failed to demonstrate its effect on stock returns.Key words: inflation, gross domestic product, exchange rotes and stock returns